Basic Anatomical Study of Pollen, Stigma, and Sheath in Bougainvillea Flowers - Sanjayanti, Arum; Alamsyah, Mashudi; Utari, Alim Diaz Tri (Journal of Biological Science and Education, 2024)
It is important to study the basic anatomy of pollen, pistils and midribs of bougainvillea flowers to improve the quality of plant reproduction, breeding and improving varieties, as well as optimizing the use of bougainvillea as ornamental plants. Bougainvillea plants have various varieties, there are three varieties sampled in this research, namely pink paper flowers (Bougainvillea bambino baby lauren), orange paper flowers (Bougainvillea afterglow), and purple paper flowers (Bougainvillea barbara karst). This research aims to determine the anatomical structure of pollen, stigma and midrib of bougainvillea plants.  This research method uses descriptive methods. The sampling technique used was purposive sampling and sample measurement under a light microscope with 10x magnification. The results of the research show that three varieties of paper flowers, namely Bougainvillea bambino baby lauren, Bougainvillea afterglow, and Bougainvillea barbara karst, all three have pollen that allows the trichoporate type, with finger-shaped, rather slender, and elongated stigmas. then the long petals are orange, pointed or slightly curved, and layered around the original flower. Furthermore, the stigma of each flower has a color that matches the color of the sheath. This research provides a reference for bougainvillea flower variability, reproductive ecology, and genetics in context and conservation.